Functional Classification of Skinning Injury Responsive Genes in Storage Roots of Sweetpotato - Effendy, Jollanda; Efendi, Darda; Khumaida, Nurul; Wattimena,; Gustaaf Adolf (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2017)
Skinning injury in sweetpotato due to loss of skin or periderm which occurred during harvest is inevitable and account for financial loss due to dehydration, pests, and pathogens. Hence, studies on gene expression changed due to skinning injury can provide important information about this protective tissue and for improving the life of storage roots. New candidate genes involved in skinning injury were isolated with an Annealing Control Primer (ACP). Using 20 ACP primers, a total of 103 differentially expressed genes (DEGs) were retrieved. In this study, the functional annotation of these selected 15 up-regulated DEGs (10 contigs and 5 singletons) were characterized. The results showed that these 15 “DEG-unigenes” are mainly associated with defense and stress responses, regulation and signaling, protein synthesis and fate, and metabolism may play an important role in the primary responses to skinning injury in storage roots of sweetpotato. This study showed the importance of defense and stress responses genes to the formation of wound periderm. Furthermore, this results can be used for better understanding of the molecular mechanism of skinning/mechanical injury-related genes in the storage roots of sweetpotato as well as to all stems, fruits, and roots of all plants. Keywords: differentially expressed gene, gene function, Ipomoea batatas, wounding